Jianghuaimon dabiense gen. nov. et sp. nov (Crustacea: Decapoda: Potamidae), a new genus and new species of freshwater crab from eastern-central China - Zhao, Jun-Da; Xu, Yi-Yang; Huang, Chao (Zootaxa, 2022)
A new genus and new species of freshwater crab, Jianghuaimon dabiense gen. et sp. nov., is described from Anhui and Hubei Provinces of China based on morphology and mitochondrial 16S rDNA sequences. Externally, the new genus resembles several other potamid genera from China. However, its combination of carapace, male pleon, third maxilliped, and uniquely structured male first gonopod distinguish it from the others. Phylogenetic analysis using the 16S gene supports the new genus new species and shows that it, together with morphologically similar Neilupotamon and Bottapotamon, form a distinct clade.